The Model of Employee Presenteeism: A Systematic Review of Studies with a Meta-Synthesis Approach - Hamed Dehghanan; Maghsoud Amiri; Mehdi Yazdanshenas; Mahdi Ghafoorifard (Taṣvīr-i salāmat, 2023)
Background. The health of employees and the work environment is important for any organization, but some organizational phenomena challenge this issue. One of the emerging organizational phenomena is presenteeism, which causes an employee to decide to be at work despite being sick (physical or mental) and feeling unwell. The aim of the current research is to provide a model of employee presenteeism based on factors affecting this behavioral phenomenon. Methods. In this study, by Meta-synthesis method, all the researches of reliable databases that were related to the research topic from 1991 to 2022 were systematically examined and finally, following the entry and exit criteria, 78 articles were identified and analyzed. Results. The results showed that the most important factors affecting employee attendance can be designed in the form of a three-dimensional model with 13 core categories and 60 components. In this model, three main dimensions include behavioral, structural and contextual dimensions. 13 core categories also include organizational characteristics and procedures, job characteristics, human resources management of the organization, organizational culture, health status of the individual, employee's attitude and perception towards the consequences of absenteeism or presenteeism, Organizational communications and interactions, Individual characteristics, Individual personality, Job and organizational attitude, Cultural and social factors, Economic factors of society and Legislation and infrastructure. Conclusion. The results of the synthesis and analysis of 78 articles in this research showed that presenteeism is a complex and multidimensional phenomenon that is caused by various factors, and the correct management of this behavior in the organization depends on careful attention to the pattern identified in this research.